First-Principles Study of Electronic and Magnetic Properties of Anatase and its Role in Anatase-Mxene Nanocomposite (Journal of Nepal Physical Society, 2019)
The electronic and magnetic properties of Titanium and one of its oxide Anatase are calculated by using Tight Binding Linear Muffin-Tin Orbital Atomic Sphere Approximation (TB-LMTO-ASA) method under Density Functional Theory (DFT). The lattice parameter, band structure, Density of States (DOS) and charge density distributions of Ti and TiO2 (Anatase) required for electronic structure are calculated respectively. The orbital contribution is analyzed by fat band structure; the d- orbital on conduction band and, s and p orbitals on valance bands. Consequently, their magnetic properties are checked. From our study, we found that the magnetic moments of Ti and TiO2 are found to be 2.2 μB and 0 respectively. The total Density of States for spin up and down electron have smaller difference in Ti and symmetric in TiO2 indicates that Ti slightly paramagnetic and Anatase is non magnetic in nature. The charge density plots reveals the concentration of electrons at the site under study. Anatase can be deposited onto Mxene to form Mxene-Anatase nanocomposite which has several excellent applications in the field of biosensors, biocompatible materials, energy storage devices, topological insulators etc.